The Influence of Population Administrative Policy Implementation on the Quality of Id Card Service - Liando, Daud M (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2013)
The research aims to analyze the influence of population administrative policy implementation on the quality of ID card service in South Minahasa District. The variables used are policy standards and objectives, policy resources, inter-organizational communication, the characteristics of the implementation agencies, the economic, social and political environment, and response of the implementers. The result shows that the implementation of population administrative policy is very much determined by the communication factor. One of the factors causing the inefficiency of ID card service is the inadequate role of society in the implementation of population administrative policy. The implementation agencies from the Office of Population and Civil Administration must ceaselessly build both vertical and horizontal communications with South Minahasa people.